Sustainable remediation of heavy metal contaminated soil through phytostabilization with the in-situ immobilization by mercapto-based palygorskite - Kuang, Hongjie; Wu, Bin; Peng, Fengge; Yu, Yahui; Ma, Xiaohui; Shangguan, Yuxian (Frontiers in Plant Science, 2025)
Phytostabilization has been widely applied to remediate mining soils contaminated with heavy metals, but the high soil toxicity often restricts plant growth and remediation efficiency. In this experiment, we investigated the effect of mercapto-based palygorskite (MPAL, applied at 2% and 4% w/w) on cadmium (Cd) and lead (Pb) phytostabilization by Chrysopogon zizanioides in soils contaminated with Cd and Pb. The results showed that soil pH did not vary under the application of MPAL but decreased during the cultivation of C. zizanioides. Compared with planting C. zizanioides alone, the application of MPAL significantly promoted the growth of C. zizanioides, enhanced its antioxidant enzyme activities, and decreased Cd and Pb concentrations in roots and shoots. Compared with CK, the addition of 4% MPAL, cultivated with C. zizanioides, reduced DTPA-extracted Cd and Pb in soils by 89.22% and 51.18%, respectively, at the highest level (p < 0.05). Moreover, urease, cellulase, and sucrase activities in soils treated with MPAL and cultivated with C. zizanioides were enhanced, with maximum increases of 37.70%, 110.22%, and 42.99%, respectively (p < 0.05). The interaction of MPAL and C. zizanioides increased bacterial richness and diversity but did not alter the bacterial community. This study demonstrated that the use of MPAL in combination with C. zizanioides could serve as a potential strategy for Cd and Pb immobilization and improvement of soil microecological properties.